Dextrocardia and DORV with Recurrent Supraventricular Tachycardia: A Very Rare Condition - Putri, Aisyah; Cenisia; Hendrawan, Yuvian; Kikuko, Irawati Hajar; Putri, Alisia (Cardiovascular and Cardiometabolic Journal (CCJ), 2026)
Background: Dextrocardia and DORV are rarely congenital heart disease. One of the life-threatening complications of CHD is arrhythmia. Supraventricular arrhythmia is the most common type of arrhythmia in adult patients with CHD. This case report aims to improve current knowledge by providing a clinical description of Dextrocardia and DORV with Recurrent Supraventricular Tachycardia. Case Report: A 24-year-old man who came to our emergency with palpitation and dyspneu. This complaint was a recurring incident that causes the patient to be readmitted to the emergency departement. Clinical examinations showed tachypnea, tachycardia, and cyanosis. Through additional physical and supporting examinations, the patient was diagnosed with dextrocardia and DORV with recurrent supraventricular tachycardia.  Conclusion: One of the most common complications of complex CHD in adulthood is supraventricular tachycardia. CHD can trigger recurrent SVT due to the presence of different anatomical and electrophysiological pathways. This condition is relapsing and became the reason for hospital admission. Appropriate therapies during acute phase and rate control are important to prevent recurrence. Keywords: Dextrocardia; DORV; SVT -- Highlights: 1. This case report describes a rare combination of dextrocardia and double outlet right ventricle complicated by recurrent supraventricular tachycardia, illustrating the complex interplay between structural abnormalities and arrhythmic risk. 2. It emphasizes that altered cardiac anatomy in congenital heart disease can predispose to persistent arrhythmias, requiring careful acute management and long-term strategies to prevent recurrence and repeated hospitalization